2022
DOI: 10.1055/s-0042-1742328
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Oral Normal Variance in Healthy Elderly Patients: A Descriptive Study on Oral Pseudo-Lesions

Abstract: Introduction The aging process in the elderly can change the condition of the oral cavity, regarding both clinical appearance and function. The oral mucosa becomes more susceptible to mechanical damage and irritant agents. Any changes in the oral mucosa, including normal variance, should be examined. This is especially true for the elderly, to improve oral health and prevent any abnormalities. Objective To describe the prevalence of oral normal variance in healthy elderly patients. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…17 In comparison, in the Dental Hospital Airlangga University, the prevalence of fissured tongue in healthy elderly (without degenerative diseases, including hypertension) also showed similar result with a percentage of 93.1%. 18 Based on the result of this study, elderly who take amlodipine were as many as 125 (8.57%) and in proportion with the numbers of participant who suffered fissured tongue.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…17 In comparison, in the Dental Hospital Airlangga University, the prevalence of fissured tongue in healthy elderly (without degenerative diseases, including hypertension) also showed similar result with a percentage of 93.1%. 18 Based on the result of this study, elderly who take amlodipine were as many as 125 (8.57%) and in proportion with the numbers of participant who suffered fissured tongue.…”
Section: Discussionmentioning
confidence: 82%
“…Other studies found a lower prevalence of crenated in healthy elderly with a prevalence of 27.59. 18 Crenated tongue may develop due to various factors involving tongue pressure, including habits such as pressing the tongue against the teeth, pushing or sucking on the tongue, bruxism, macroglossia, and tongue thrusting. 24 Management of crenated tongue focuses on treating the underlying cause and promoting oral health.…”
Section: Total Subjects 147mentioning
confidence: 99%
See 1 more Smart Citation